Reconstructing Late Quaternary precipitation and its source on the southern Cape coast of South Africa: A multi-proxy paleoenvironmental record from Vankervelsvlei. (15th May 2022) - Strobel, P.; Bliedtner, M.; Carr, A.S.; Struck, J.; du Plessis, N.; Glaser, B.; Meadows, M.E.; Quick, L.J.; Zech, M.; Zech, R.; Haberzettl, T.
Abstract: The Late Quaternary climate history of South Africa and, in particular, potential changes in atmospheric circulation have been subject to considerable debate. To some extent, this is due to a scarcity of natural archives, and on the other hand the available indirect hydrological proxies are not suited to distinguishing between precipitation originating from temperate Westerlies and tropical Easterlies. This study presents a paleoenvironmental record from Vankervelsvlei, a wetland located on the southern Cape coast in the year-round rainfall zone of South Africa. A 15 m long sediment record was retrieved from this site and analysed using a multi-proxy approach. This includes, for the first time in this region, analysis of both compound-specific δ 2 H and δ 18 O from leaf wax-derived n -alkanes and hemicellulose-derived sugars, respectively, to investigate hydrological changes during the Late Quaternary. Our data suggest the driest conditions of the past ∼250 ka likely occurred from MIS 6 to MIS 5e, which still caused sediment deposition at Vankervelsvlei, and MIS 2, during which time there was an absence of sedimentation. Moist conditions occurred from MIS 5e to 5a and during parts of MIS 3, while drier conditions prevailed between MIS 5a and early MIS 3 and at the transition from MIS 3 to MIS 2. Besides changes in the amount and proportional contribution of precipitation contributions from Westerlies during glacial and Easterlies during interglacial periods, relative sea-level change affected the continentality of Vankervelsvlei, with a distinct impact on the sites hydrological balance. High-resolution analyses of the Middle- and Late-Holocene parts of the record show moist conditions and increased Easterly/locally-derived summer precipitation contributions from 7230 +160 /−210 to 4890 +280 /−180 cal BP and after 2840 +350 /−330 cal BP. Dry conditions, accompanied by the reduction of Easterly/locally-derived summer rainfall and increased seasonality occurred from 4890 +280 /−180 to 2840 +350 /−330 cal BP. Our findings highlight that source and seasonality of precipitation play a major role in the hydrological balance of the southern Cape coastal region. By comparing the Vankervelsvlei record to other regional studies, we infer a coherent trend in the overall moisture evolution along South Africa's southern Cape coast during the Late Quaternary. Highlights: Comprehensive investigation of peat sediments from South Africa's southern Cape coast. Application of the coupled δ 2 H n -alkane –δ 18 Osugar paleohygrometer approach. Local moisture is driven by past changes in sea level and atmospheric circulation patterns during the Late Quaternary. Holocene moisture availability along the southern Cape coast is driven by precipitation contributions from local sources.